Luteal-phase inhibin A and follicular-phase inhibin B levels are not characteristic of patients with an elevated LH-to-FSH ratio - Hauzman, Erik E. (Springer US, 2006)
Purpose: To test whether serum inhibin levels are related to differences in gonadotropin concentrations between patients with an elevated LH-to-FSH ratio (ELF patients) and controls. Methods: 32 ELF patients were matched with controls by age, body mass index (BMI), and cycle length. Results: No statistically significant difference was found in follicular-phase inhibin B levels or midluteal inhibin A levels between cases and controls. Significant negative correlation was observed between follicular-phase inhibin B concentrations and BMI in ELF patients but not among controls. LH and FSH were positively related to inhibin B levels in ELF patients. Midluteal inhibin A correlated with sex hormone-binding globulin in controls but not in ELF patients. Conclusions: Neither follicular-phase inhibin B levels nor midluteal inhibin A levels are characteristic of patients with an elevated LH-to-FSH ratio. Opposite correlations with LH and BMI suggest dysregulation of inhibin secretion rather than dimeric inhibins having a central role to the endocrinological imbalance observed in polycystic ovary syndrome.